KEMAMPUAN FUNGSIONAL LANSIA DI UPT PANTI WERDHA “MAJAPAHIT” MOJOKERTO - MUHITH, ABDUL (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2010)
By progressing someone’s age, they will get dcreasing especially in function abiliy that causes decreasing in their role of social. This why it also raises some troubles in their lifes until they can need other’s helping because of depending on them. The aim of this research is to know function the old in UPT Panti Werda Mojopahit of Mojokerto. The method design of this research is descriptive by population of all the old who stay at UPT Panti Werdha and its sample is who stays at UPT Panti Werdha by sampling Purposive technic. Collecting data by observation, interview and instrument uses checklish according to Index Barthel modificated. The variable of this research is the old’s ability function. Anaylising data technic is used by frequency distribution. The result of this research, from 41 respondences, they get modern depending on daily activities in Index Barthel is 10 self the old (24,4%), 9 the old (21,9%) have less depending, 15 the old (36,6%) have modern depending, 5 the old (12,2%) have the excess depending or very dependending and the least 2 the old have full depending (4,9%). The estimated is the woman 2 times often fallen than the man.The conclusion above is the most respondence have modern depending of 15 the old (35%) dan more than 50% have depending is the woman. they are 25 the old (60%), more than 50% the old who stay at Panti Werdha Mojopahit of Mojokerto are elderly that is 60-74 old get 25 respondences (71%). Key words: funtion ability, the old